2020
DOI: 10.7759/cureus.6754
|View full text |Cite
|
Sign up to set email alerts
|

Tumefactive Multiple Sclerosis of the Cervical Spinal Cord: A Rare Case Report

Abstract: Tumefactive multiple sclerosis (TMS) is a rare variant of multiple sclerosis (MS) with atypical features that pose a diagnostic challenge. In this study, we report a case of cervical MS in a 19year-old patient that was diagnosed based on the MRI findings and cerebrospinal fluid analysis. The patient was treated with high-dose steroid and five sessions of plasma exchange with significant improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…TMS is an uncommon variant of MS characterized by tumefactive demyelinating lesions (TDLs) larger than 2 cm and may be associated with mass effect and/or edema; it is often cannot be differentiated from CNS neoplasms, especially glioma and CNS lymphoma [ 3 , 6 ]. TMS is estimated to affect 1-3/1,000 MS cases, with an annual incidence of 0.3/100,000 people [ 8 ]. TDLs are not an uncommon manifestation of demyelinating disease, with an incidence of 2.8% of MS cases.…”
Section: Discussionmentioning
confidence: 99%
“…TMS is an uncommon variant of MS characterized by tumefactive demyelinating lesions (TDLs) larger than 2 cm and may be associated with mass effect and/or edema; it is often cannot be differentiated from CNS neoplasms, especially glioma and CNS lymphoma [ 3 , 6 ]. TMS is estimated to affect 1-3/1,000 MS cases, with an annual incidence of 0.3/100,000 people [ 8 ]. TDLs are not an uncommon manifestation of demyelinating disease, with an incidence of 2.8% of MS cases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, relative to brain abscesses and tumors the mass effect along with edema in TMS are proportionally smaller relative to plaque size. It has been suggested that the lack of mass effect differentiates MS plaques from other space-occupying lesions (11,22,23).…”
Section: Imagingmentioning
confidence: 99%
“…Most TDL demonstrate increased DWI and ADC signals on MRI, allowing differentiation of lymphomas with a water diffusivity restriction that makes them hyperintense on DWI and hypointense on ADC maps. Occasionally, acute demyelinating lesions may have areas of diffusion restriction with reduced ADC values at the periphery of the lesion (6,23,25).…”
Section: Imagingmentioning
confidence: 99%